THE IMPACT OF FRAILTY ON DISEASE PROGRESSION OF SYSTEMIC SCLEROSIS: A HYPOTHESIS - Neslihan Gokcen (Anti-Aging Eastern Europe)
Frailty, a multidimensional syndrome marked by diminished physiological reserve and increased vulnerability, hasemerged as a critical concern in systemic sclerosis (SSc). Both age-related inflamm-aging and disease-related chronicinflammation contribute to the higher prevalence of frailty in SSc patients compared to their age-matched counterparts. Frailty in SSc is strongly associated with adverse outcomes, including skin involvement, increased disability, physical inactivity, higher hospitalization rates, malnutrition, severe gastrointestinal symptoms, interstitial lung disease, and elevated mortality. This hypothesis posits frailty as an overlooked factor in the progression and severity of SSc. Early identification of frailty at its pre-frailty stage is essential. Implementing targeted preventative strategies could mitigate its impact, significantly enhancing long-term disease management and clinical outcomes for patients with SSc.